1992
DOI: 10.1177/002224299205600404
|View full text |Cite
|
Sign up to set email alerts
|

First-Mover Advantage: A Synthesis, Conceptual Framework, and Research Propositions

Abstract: Numerous conceptual and empirical studies advance the notion that first movers achieve long-term competitive advantages. These studies purport to demonstrate the presence of a systematic direct relationship between order of entry for products, brands, or businesses and market share. However, an objective assessment of the literature suggests that this view must be qualified. A broadened perspective is presented that highlights the complexity of this phenomenon and suggests that first-mover status may or may no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
272
0
4

Year Published

1996
1996
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 566 publications
(285 citation statements)
references
References 34 publications
9
272
0
4
Order By: Relevance
“…Hence, a more feasible plan for the technology deficient firms would be to develop innovative technology on their own in a phased manner, but in the meantime to focus on applying any less advanced technology that is readily available at less expense. Thus, the preferred catch up strategy during the initial stages would be that of being efficient rather than being effective (Kerin, Varadarajan, & Peterson, 1992). Therefore, technology deficient firms in emerging economies often prefer to imitate what is readily available rather than search for cutting-edge technologies and differentiate their offerings in terms of cost.…”
Section: Implications For the Initial Catching Up Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, a more feasible plan for the technology deficient firms would be to develop innovative technology on their own in a phased manner, but in the meantime to focus on applying any less advanced technology that is readily available at less expense. Thus, the preferred catch up strategy during the initial stages would be that of being efficient rather than being effective (Kerin, Varadarajan, & Peterson, 1992). Therefore, technology deficient firms in emerging economies often prefer to imitate what is readily available rather than search for cutting-edge technologies and differentiate their offerings in terms of cost.…”
Section: Implications For the Initial Catching Up Processmentioning
confidence: 99%
“…Acceptance of the firm as a long-term player by the firm's stakeholders in the value chain, primarily its customers and suppliers, is a very important form of legitimacy (Ahlstrom & Bruton, 2001;Kerin et al, 1992). Firms need legitimacy because, from the point of view of customers, only those which offer quality products consistently would be seen as firms that are serious about staying in the market (Kerin et al, 1992). Secondly, when a key component is in heavy demand, the suppliers will cater first to the needs of those firms that they expect to stay in the industry (Ahlstrom & Bruton, 2001).…”
Section: Implications For the Initial Catching Up Processmentioning
confidence: 99%
“…For example, several studies have reported failure rates in the 20-40% range (Calantone, di Benedetto, and Bhoovaraghavan, 1994). A common representation of product development strategy is the innovativeness of new products introduced into new or existing markets (e.g., Kerin et al, 1992;Varadarajan and Clark, 1994). Developing innovative products or being the first-mover with a new product concept is the most risky product development strategy due to the difficulty of correctly identifying new product opportunities, uncertain technological standards, existence of competitors with established products that fulfill the same generic need, and buyer resistance to innovation.…”
Section: Market Orientation and Product Innovationmentioning
confidence: 99%
“…Early followers are imitators that reduce risk by observing pioneers' successes and failures, and by taking advantage of free-rider effects through lower development and manufacturing costs. Late followers or defenders are the most risk averse in that they prefer to grow by further penetrating their traditional markets, and postpone new product development and market entry until the market's potential is demonstrated and technological standards are well established (e.g., Miles and Snow, 1978;Lieberman and Montgomery, 1988;Kerin et al, 1992;Slater, 1993).…”
Section: Market Orientation and Product Innovationmentioning
confidence: 99%
See 1 more Smart Citation